2013
DOI: 10.1177/2158244013503964
|View full text |Cite
|
Sign up to set email alerts
|

Training of Library Assistants in Academic Library

Abstract: The purpose of this research is to identify the need to train and retrain library assistants in academic libraries. The researchers however used Babcock University Library to ascertain the impacts of training of library assistants. A descriptive design was adopted for this study. A total enumeration sampling method was used. The instrument used for data collection was a structured questionnaire. The population was made up of 30 respondents who were library assistants at the Babcock University Library, Nigeria.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 4 publications
1
21
0
Order By: Relevance
“…The junior library staff are left to man major duties (see Table 7). This finding is in line with that of Bamidele, Omeluzor, Imam, and Amadi's (2013) study which indicates that among the library assistants, 86.7% had Senior School Certificate of Education (SSCE). This adversely affected service delivery to library clients as this low level of staff did not have required skills, knowledge, and training to man major duties.…”
Section: Discussion Of Findingssupporting
confidence: 91%
“…The junior library staff are left to man major duties (see Table 7). This finding is in line with that of Bamidele, Omeluzor, Imam, and Amadi's (2013) study which indicates that among the library assistants, 86.7% had Senior School Certificate of Education (SSCE). This adversely affected service delivery to library clients as this low level of staff did not have required skills, knowledge, and training to man major duties.…”
Section: Discussion Of Findingssupporting
confidence: 91%
“…Back in Nigeria, a careful search of the literature revealed that not much work has been carried out in this regard. However, in their study on training of library assistants in an academic library in Nigeria, Bamidele et al (2013) found that paraprofessionals needed competencies in the area of system management and web searching. Availability and utilization of training programmes is a viable avenue through which paraprofessionals can enhance their competencies.…”
Section: Literature Reviewmentioning
confidence: 98%
“…This reflection indicates how the demands of Covid-19 and the shift to distance-learning prompted changes to staff responsibilities. The literature relating to the professional relationship between Librarians and support staff has touched upon the importance of continual professional development (Bamidele et al, 2013). Indeed, their key observation is that the "training of library assistants will enhance efficient service delivery, adequate user satisfaction, increased productivity, and improved quality of work" (p.8).…”
Section: Reflection On the Covid-19 Distance Learning Experiencementioning
confidence: 99%
“…However, the analysis does not include the role of support staff in these practices. Bamidele et al (2013) highlight the significance of upskilling support staff in using online resource technologies, but the study does not explore these roles, nor does it discuss the relationship of the two within online teaching environments. Indeed, the observations about the changing nature of roles during Covid-19 is not an isolated phenomenon.…”
Section: Reflection On the Covid-19 Distance Learning Experiencementioning
confidence: 99%